2020
DOI: 10.3390/ma13102394
|View full text |Cite
|
Sign up to set email alerts
|

Study of Carbon Black Types in SBR Rubber: Mechanical and Vibration Damping Properties

Abstract: Styrene–butadiene rubber mixtures with four types of carbon black were studied in this paper. The mechanical properties, including the ability to damp mechanical vibration, were investigated, along with dynamical mechanical analysis (DMA). It has been found that carbon black types N 110 and N 330, having the largest specific surface area and the smallest particle diameter, provide a good stiffening effect. These particles have significant interactions between the rubber, resulting in good reinforcement. On the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(15 citation statements)
references
References 32 publications
0
8
0
Order By: Relevance
“…Styrene-butadiene rubber (SBR) is a synthetic rubber with about 70% usage in the rubber industry. 1,2 Styrene content varies between 24% and 46% depending on the stiffness required. 3 Among reinforcing fillers, carbon black and silica are the most common fillers used in the composition of tire, especially the tread part.…”
Section: Introductionmentioning
confidence: 99%
“…Styrene-butadiene rubber (SBR) is a synthetic rubber with about 70% usage in the rubber industry. 1,2 Styrene content varies between 24% and 46% depending on the stiffness required. 3 Among reinforcing fillers, carbon black and silica are the most common fillers used in the composition of tire, especially the tread part.…”
Section: Introductionmentioning
confidence: 99%
“…Neural network is a relatively systematic and accurate control method in the trajectory tracking control of mechanical arm, which provides an effective way to study the modeling and control of mechanical arm. It can ensure that the position and velocity tracking errors of the end effector of the mechanical arm gradually converge to zero [6,7]. Aiming at the problems of closedchain structure, unknown dynamic parameters, and strong coupling in coordinated multi-mechanical arm systems, a position-force hybrid control strategy was designed based on fuzzy neural network.…”
Section: Introductionmentioning
confidence: 99%
“…On the contrary, resilience decreases, which that the relationship between resilience and carbon black loading levels is inverse. Pöschl et al [16] investigated the influence adding of different kinds of carbon black at the same loading of level for all these kinds of carbon black on the mechanical characteristics as well as the capacity to dampen mechanical vibrations for the styrene-butadiene rubber. They found that the (SBR) mixture has good stiffness at adding (N110 and N330).…”
Section: Introductionmentioning
confidence: 99%